Quantitative Theory for the Electrical Breakdown of High‐Temperature Dielectric Materials under High Temperature and Electric Field. Issue 10 (14th July 2022) - Wang, Ruzhuan; Li, Weiguo
Abstract: The electrothermal breakdown of high‐temperature dielectric materials has received increasing attention. However, the theoretical characterization of quantitative relationship between breakdown strength and temperature has been a challenge. Herein, a theory termed energy storage capacity has been developed to generate and understand the nature of this quantitative relationship. This theory defines a limit value of stored energy associated with the material breakdown, including electric energy and the equivalent heat energy. Then, a parameter‐free theoretical model of temperature‐dependent breakdown strength of materials is developed, which takes into account the effects of dielectric constant and melting point. This non‐fitting model, without the need to carry out any destructive experiments and data fitting, is validated with excellent agreement between the predicted and measured values of both polymers and ceramics, monolithic and multilayered polymer/ceramic composites. It is shown that the failure of large classes of substances, including ceramics and polymers under heat and electrical force or mechanical force can be accurately modeled using the concept of the temperature independent limit value of the stored energy. This should become the new insight and entry point for the development of quantitative characterization of temperature‐dependent physical and mechanical properties of materials. Abstract : This study is concerned with developing a quantitative theory for describing the temperature dependence of breakdown strength of high‐temperature dielectric materials. It is shown that the failure of large classes of substances including ceramics and polymers under heat and electrical force or mechanical force can be accurately modeled using the concept of energy storage capacity, with a unified characteristic form.